Предмет: Математика,
автор: ZZZ1233214
6*(b-3)=10-2*(b+2)
83+5*(y-3)=3*(8y-9)
Ответы
Автор ответа:
0
6*(b-3)=10-2*(b+2)
6b-18=10-2b-4
6b+2b=10+18-4
8b=24
b=24:8
b=3
83+5*(у-3)=3*(8у-9)
83+5у-15=24у-27
5у-24у=15-27-83
-19у=-95
19у=95
у=95:19
у=5
6b-18=10-2b-4
6b+2b=10+18-4
8b=24
b=24:8
b=3
83+5*(у-3)=3*(8у-9)
83+5у-15=24у-27
5у-24у=15-27-83
-19у=-95
19у=95
у=95:19
у=5
Похожие вопросы
Предмет: Русский язык,
автор: ajtekingiasova7204
Предмет: Литература,
автор: Аноним
Предмет: Английский язык,
автор: Kristinaponomareva20
Предмет: География,
автор: Борунова